An improved method for measuring hip abduction in spica after surgical reduction for developmental dysplasia of the hip - DeFrancesco, C. J. (J Child Orthop, 2017)
PURPOSE: Excessive in-spica abduction is a risk factor for oste-onecrosis after surgical reduction for developmental dysplasia of the hip (DDH). The traditional method for radiographically measuring hip abduction using axial imaging does not reflect the true angle, which usually lies in an oblique plane. The purpose of this study was to describe a novel method for measuring true hip position using advanced imaging. METHODS: A trigonometric model was derived to define hip position based upon the femoral axis angular deviation from midline as measured on axial and coronal sequences of MRI studies. In-spica MRIs of 28 hips having undergone surgery for DDH were reviewed. On two separate occasions, the same three raters measured the femoral axis deviation from mid-line on axial and coronal imaging. Abduction was estimated using the traditional method of measurement and our novel method. Intra- and inter-rater reliability were assessed. RESULTS: The methods yielded different estimates (p < 0.001). Inter- and intra-rater reliability were excellent for both methods (inter-rater ICC > 0.922, intra-rater ICC > 0.919). The traditional method is accurate at 90° of flexion, but it increasingly overestimates abduction as hip flexion decreases. All cases where hip flexion was ≤ 40° exhibited ≥ 10° of error. CONCLUSIONS: Decreasing hip flexion in spica modifies the perceived angle of abduction as measured using axial imaging. This inaccuracy can be overcome through assessment of orthogonal views using our new approach, which is accurate and reliable. It should be considered for future research investigating the effects of in-spica hip position on outcomes of DDH treatment.